Adapting an attention-deficit hyperactivity disorder parent training intervention to different cultural contexts: the experience of implementing the New Forest Parenting Programme in China, Denmark, Hong Kong, Japan and the United Kingdom - Daley, David (Wiley, 2017)
Attention Deficit Hyperactivity Disorder (ADHD) is a highly prevalent disorder affecting around 4% of preschool and school-aged children worldwide (Egger & Arnold, 2006; Polanczyk et al 2007). The presence of ADHD in preschool age children is associated with a clear risk of later educational difficulties (Washbrook et al. 2013) and ADHD leads to family borne costs (e.g. time off work, cost of damage in the home) as well as increased health and education costs (Chorozoglou et al, 2015). The challenges of bringing up a child with ADHD are compounded when parents lack social and educational resources to cope with and manage that child’s difficult and challenging behaviour (Larsson et al, 2014).